Double Proton Transfer in the Dimer of Formic Acid: An Efficient Quantum Mechanical Scheme - Liu, Hao; Cao, Jianwei; Bian, Wensheng (Frontiers in Chemistry, 2019)
Double proton transfer plays an important role in biology and chemistry, such as DNA base pairs, proteins and molecular clusters, and the direct information about these processes can be obtained from tunneling splittings. Carboxylic acid dimers are prototypes for multiple proton transfer, in which the formic acid dimer is the simplest one. Here, we present efficient quantum dynamics calculations of ground-state and fundamental excitation tunneling splittings in the formic acid dimer. These are achieved with a multidimensional scheme developed by us, in which the saddle-point normal coordinates are chosen, the basis functions are customized for the proton transfer process, and the preconditioned inexact spectral transform method is used to solve the resultant eigenvalue problem. Our computational results are in excellent agreement with the most recent experiments [Angew. Chem. Int. Ed. 2019, 58, 859; J.Chem.Phys., 2017,146,244306].